Media Komunikasi Digital PolisiKu: Pelayanan Publik Polri kepada Masyarakat - Prabowo, Tyan Ludiana; Irwansyah, Irwansyah (Faculty of Communications Science, Dr. Soetomo University, 2018)
Industrial Revolution 4.0 has changed human life. Humans become dependent on device connectivity, product digitisation and service and information access openness. This study discusses my Police application. National Police's first national online application. This application is the result of 26 online applications that were previously built separately by work units and territorial units within the National Police. My police are integrated to improve services for the people of Indonesia. This research is used to adapt and apply Information and Communication Technology to the Community in realizing digital-based community services. The method used is research, to get insights from the application, the way adaptation is done by POLRI personnel with the presence of the technology and how it is applied in implementing digital services to the community. The results obtained show that the Police of Baintelkam officers have not been able to adapt to the connectivity of SKCK services, data relating to blood and legality of the legality of community leaders. In addition, for Personnel Readiness, traffic, moderation facilities have not been evenly distributed, access to Online SIM access has not been established nationally. Meanwhile, only the Information Technology Division and Baharkam and Criminal Investigation Offices are ready with Police Post data and Emergency Call services, because of the back-office system from the center to the police station to assist with the operation and digitization of police services in my police.